2012
DOI: 10.1162/jocn_a_00127
|View full text |Cite
|
Sign up to set email alerts
|

Attentional Capture by Salient Distractors during Visual Search Is Determined by Temporal Task Demands

Abstract: ■ The question whether attentional capture by salient but taskirrelevant visual stimuli is triggered in a bottom-up fashion or depends on top-down task settings is still unresolved. Strong support for bottom-up capture was obtained in the additional singleton task, in which search arrays were visible until response onset. Equally strong evidence for top-down control of attentional capture was obtained in spatial cueing experiments in which display durations were very brief. To demonstrate the critical role of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
150
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 157 publications
(167 citation statements)
references
References 23 publications
17
150
0
Order By: Relevance
“…These findings confirm the N2pc evidence for successive feature-based and object-based attentional control processes and for the parallel operation of feature-based attentional selectivity across different locations in the visual field that was obtained in our main experiment. They also demonstrate that these mechanisms are not specific to data-limited situations with brief search displays, but are also activated when the temporal demands on attentional selectivity are less extreme (see Kiss, Grubert, Petersen, & Eimer, 2012, for the existence of other qualitative differences of attentional control processes under conditions of high versus low temporal task demands).…”
Section: Discussionmentioning
confidence: 92%
“…These findings confirm the N2pc evidence for successive feature-based and object-based attentional control processes and for the parallel operation of feature-based attentional selectivity across different locations in the visual field that was obtained in our main experiment. They also demonstrate that these mechanisms are not specific to data-limited situations with brief search displays, but are also activated when the temporal demands on attentional selectivity are less extreme (see Kiss, Grubert, Petersen, & Eimer, 2012, for the existence of other qualitative differences of attentional control processes under conditions of high versus low temporal task demands).…”
Section: Discussionmentioning
confidence: 92%
“…This component, which we call the posterior positivity, appeared to persist for a longer time on trials on which the observer failed to report the target, and it had a scalp topography that was similar to that of the N2 but opposite in polarity. This posterior positivity may be related to the Pd component (Kiss et al, 2012;Luck & Hillyard, 1994;Sawaki, Geng, & Luck, 2012;Sawaki & Luck, 2010) that is elicited by task-irrelevant distractors in attentional capture paradigms. Such distractors have been found to elicit an N2pc, followed by a Pd, which may reflect a sequence of engagement and disengagement of attention with respect to the distractor object.…”
Section: Discussionmentioning
confidence: 93%
“…The subtraction topography shows a bilateral, posterior positivity over occipital temporal areas that is slightly larger over the right hemisphere than over the left. We will refer to this as the posterior positivity component, although we speculate in the discussion that it might be identical to the P D component that is elicited by salient, task-irrelevant singletons in visual search tasks (Kiss, Grubert, Petersen, & Eimer, 2012;Sawaki et al, 2012;Sawaki & Luck, 2010). We quantified the average amplitude of this component using a measurement window of 405-615 ms after distractor onset.…”
Section: Posterior Positivitymentioning
confidence: 99%
“…Such short display durations may have encouraged particularly rapid attention movements, as longer dwell times at the location of fixed-color targets may have resulted in participants not being able to selectively process and identify variable-color target digits in the same display. A previous N2pc study from our lab (Kiss et al, 2012) has demonstrated that temporal task demands associated with manipulations of search display durations can have systematic effects on attentional allocation strategies. It is thus possible that the speed of moving attention from fixed-color to variable-color target objects may be considerably slower when search displays remain visible for longer, so that observers will be able to identify both target objects in the search display even with less rapid attention shifts.…”
Section: Methodsmentioning
confidence: 89%